SAT-735 Effects of Androgen Receptor Activation on Angiogenesis - Huo, Yen-Nien (J Endocr Soc, 2020)
The effect of androgen on angiogenesis has been documented. However, its molecular mechanisms underlying has not been well illustrated. Here, we conducted both in vitro migration assay and proliferation assay to investigate whether androgen receptor activation have any impacts on the angiogenesis. Treatment with an androgen receptor (AR) agonist, metribolone (R1881) at a range of concentrations (0.05-5 nM) or dihydrotestosterone (DHT) at a range of concentrations (0.5-2 nM) caused concentration-dependent inhibition of proliferation and migration in human umbilical venous endothelial cells (HUVEC). Blockade of the AR activity by pre-treatment with HF (5 nM), an AR antagonist, or knockdown of AR expression using the lenti-virus shRNA technique abolished the R1881-induced proliferation and migration inhibition in HUVEC, suggesting that AR receptor activation can inhibit endothelial cell proliferation and migration. To further delineate the signaling pathway involved in the AR activation-induced proliferation inhibition, our data indicate that R1881 inhibited proliferation in vascular endothelial cells through activating the AR/cSrc/AKT/p38/ERK/NFκB signaling pathway, which in turn up-regulated the expression of p53, p21 and p27 protein, and finally reduced endothelial cell proliferation. To investigate signaling pathway involved in the AR activation-induced migration inhibition, our data showed that R1881 can reduce the membrane translocation of RhoA and Rac-1, suggesting that inhibition of the RhoA and Rac-1 activity might be involved in the R1881-inhibited endothelial cell migration. Over-expression of RhoA prevented the R1881-inhibited endothelial cell migration and this effect was abolished by pre-treatment with Y27623, a ROCK inhibitor, confirming that inhibiting RhoA activity participated in the R1881-inhibited endothelial cell migration. Using the zebrafish and Matrigel angiogenesis models, we also demonstrated that R1881 inhibited angiogenesis through the AR-mediated pathway in vivo.